Beginning EFL teachers’ beliefs about teaching and learning in the context of secondary schools in China - Zhang, Naixin (2016)
This study examined the beliefs about English teaching and learning of six Chinese secondary school EFL teachers, whether any changes occurred in their beliefs during the first three years in the profession, and why beginning teachers changed or did not change their beliefs. Data were collected over a period of 10 months using semi-structured interviews, concept mapping, and journal entries. The findings showed how teachers’ learning in the workplace influenced change or no change in beliefs, how their schools supported learning, how teachers elected to engage in activities and how these affected the nature of their beliefs.